Dynamic speckle imaging with low-cost devices - Vannoni, Maurizio (2008)
Light from a rough sample surface illuminated with a laser consists of a speckle pattern. If the surface evolves with time, the pattern becomes dynamic, following the activity of the sample. This phenomenon is used both in research and in industry to monitor processes and systems that change with time. The measuring equipment generally includes high-performance CCD cameras and other expensive devices. Based on the same principle, here we describe a simplified approach where components and devices commonly available in undergraduate physics laboratories are instead used. The technique is described in detail, also reviewing the basic properties of speckle fields. Examples of the application are given, and suggestions for further investigation are provided.